Some aspects of the bionomics and morphology of the European house-borer, Hylotrupes Bajulus (L) (Coleoptera: Cerambycidae) and its control in the Western Cape Province - Durr, Herwil Johan Reineke (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1950.